O amigo da corte no plano subnacional: análise dos critérios adotados pelos tribunais de justiça brasileiros para admitir a participação do amicus curiae nas ações diretas de inconstitucionalidade. - Ferreira, Marina Eugênia Costa (2018)
The present work is in the field of Constitutional Law, in the area of concentration of constitutional jurisdiction and fundamental rights. Its purpose is verify the performance of the Judiciary Power of the Member States with regard to the control of constitutionality, specifically, to direct actions of unconstitutionality. To this end, it will be assumed that: (i) if the Law 9.868 / 1999, which instituted amici curiae in Brazilian legal system, specifically in the control of constitutionality in the abstract modality through ADI's, deals with the participation of these actors in the actions proposed at the STF, then, this Law has no incidence at the subnational level; (ii) if Brazil, because it is politically organized as a Federal State, has several autonomous centers of political power capable of elaborating its own Constitutions and legislative collections, observing the limits given by the Federal Constitution, then these federal entities can create their own admission criteria for amicus curiae in the processing of ADI's. Having made this introduction, and considering that the Federal Constitution of 1988, in its art. 125, §2, establishes that each member state is responsible for the constitutional control itself, not determining the respective limits, it is sought to identify the criteria required by the Brazilian Courts of Justice to admit the amicus curiae's participation in direct actions of unconstitutionality. In order to arrive at the result, a bibliographical review will be done initially on the existing literature on the Brazilian constitutional design, federalism and constitutional jurisdiction in the sphere of Member States. Then, from the perspective of the opening of the constitutional interpretation to the society and of the fundamental rights to the participation in the organization and procedure, will be studied the figure of the amicus curiae. Afterwards, statistical data obtained through the quantitative method will be presented in order to demonstrate the proportion between the number of ADI's proposed before the Brazilian Courts of Justice and in which of them there was a request for amicus curiae's participation, and then to verify how many of these were accepted by the judges. After the quantitative analysis, the qualitative examination of the dispatches and / or decisions handed down by the Courts of Justice will be carried out, in order to identify the criteria used for the deferment of the participation of the amici.